IMPLEMENTASI MODEL PROBLEM BASED LEARNING BERBANTUAN ALAT PERAGA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR FISIKA SISWA KELAS VIII SMPN 22 MATARAM - Baiq Ewik Jiniarti; Hairunnisyah Sahidu; Ni Nyoman Sri Putu Verawati (IKIP Mataram, 2015)
This research is a Classroom Action Research (CAR) which aims to increase the students activities and physics learning outcomes with implementation problem based learning model assisted by props in grade VIIIA SMPN 22 Mataram. This classroom action research conducted by two cycles, with each cycle consisting of two meetings. Action research consists of four stages: planning, implementation, observation and evaluation, and reflection. The implementation of classroom action research was successful because it obtained an average score of students learning activities from the first cycle to the second cycle was on active criterion to be very active with average scores of 16,875 to be 22,75. Cognitive learning outcomes of students with the average value of the first cycle of 74,13 with classical completeness 73,91% increased with the average value of second cycle of 79,35 with classical completeness 86,96%. Affective students learning outcomes from the first cycle to the second cycle with an average value of 66,195 to 78,95 on the criteria good enough to be good. Psychomotor students learning outcomes from the first cycle to the second cycle an average value of 71,63 to 85,655 are the criteria enough skilled become skilled. Thus, this research can be concluded by implementation of problem based learning model aided by props can increase students activities and learning outcomes of phyics grade VIIIA SMPN 22 Mataram.